Information and Communication Technologies and Poverty: The Telecentre Movement in Java - Widjajanti Mulyono Santoso (Journal of Indonesian Social Sciences and Humanities, 2011)
This article discusses telecentre development in Indonesia but focuses on case studies of telecentres in Java. The research uses twelve indicators from Rao (UNCTAD, 2006: 186) to help illustrate telecentre development. This research, which uses qualitative methods (structured interviews), is to help shape national policies that will enable communities to prosper by benefiting from information and communication technology for poverty reduction (ICT4P). It draws on the research and experience of using ICT4P internationally, nationally and in other parts of Indonesia. ICT4P is partly a global commitment by many nations, under the auspices of the United Nations, that gathered together at the World Summit on the Information Society (WSIS) in Switzerland in 2003 and in Tunis in 2005. The global commitment is to understand the different interests between poor, third-world countries and others. Therefore, in their points of agreement, promoting information and communication technology (ICT) was one of the commitments, and Indonesia has stated its target is to have 50 per cent of its people with internet connectivity by 2015. The reaction to this program varies; Jatim Province is very positive that it will now build telecentres using the UNDP–Bappenas design but will fund them from its own provincial and municipal budgets.2 Other provinces did not give it much attention, but there are other civil society initiatives to build different types of telecentres suitable for local needs.